(untitled) (International Scientific Journal Alfraganus, 2025)
In this article, the zoroastrian holy book "Avesta" describes the attitude towards the issue of education and the importance of the formation of pedagogical culture in society. Key words: youth, education, upbringing, good, evil, parent, mentor.